Physical activity and exercise during pregnancy in relation to gestational weight gain: A systematic review with synthesis without meta-analysis - Chori Elsera; Anafrin Yugistyowati; Umi Faridah; Devi Permata Sari; Marwanti (Alma Ata University Press, 2026)
Background: Excessive gestational weight gain (GWG) is associated with adverse maternal and neonatal outcomes, including gestational diabetes mellitus, hypertensive disorders, increased birth weight, and postpartum weight retention. Physical activity and structured exercise are modifiable lifestyle factors that may help prevent excessive GWG, yet evidence varies by intervention type, intensity, duration, and adherence. Objectives: This systematic review aimed to synthesize evidence from randomized controlled trials on the effects of physical activity and exercise interventions during pregnancy on gestational weight gain. Methods: This systematic review followed PRISMA 2020 guidelines and used a Synthesis Without Meta-analysis approach. Searches were conducted in PubMed, ScienceDirect, Scopus, and Emerald for studies published between 2013 and 2023. Eligible studies were randomized controlled trials involving pregnant women receiving physical activity or exercise interventions. GWG was the primary outcome, while gestational diabetes mellitus, hypertensive disorders, neonatal outcomes, and adherence were secondary outcomes. Screening was conducted using Rayyan, and study quality was assessed using the CASP checklist. Results: A total of 2,052 records were identified. After duplicate removal and eligibility screening, 27 full-text articles were assessed, and 4 randomized controlled trials were included. The included studies generally suggest that structured exercise during pregnancy may help reduce excessive GWG, although findings varied across populations and intervention characteristics. Conclusions: Physical activity and structured exercise during pregnancy may help prevent excessive gestational weight gain, although their effectiveness depends on adherence, baseline BMI, and intervention characteristics. Integrating exercise counseling into antenatal care may support appropriate gestational weight gain